2012
DOI: 10.1163/156854111x617879
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Heterodera glycines and Meloidogyne incognita infective juveniles exposed to nematode FMRFamide-like peptides in vitro

Abstract: The effects of 1 mM solutions of FMRFamide-like peptides (FLPs) on the behaviours of Heterodera glycines and Meloidogyne incognita infective juveniles (J2) were examined in vitro. Seven FLPs, representing products of five flp genes and comprising a variety of amino acid sequences, were tested for their effects on J2 head movement frequency. Distinct differences in species responses were observed. KHEYLRFa and KSAYMRFa caused increased head movement frequencies in each species. In H. glycines KHEYLRFa was 2.9-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Hg-FLP-22b and Hg-FLP-22c displayed significant stimulatory effects on head movement and stylet penetration ability compared with Hg-FLP-22a, suggesting the two peptides may be significantly more active isoforms of Hg-FLP-22 for activation of putative cognate receptors. Similar observations were also reported by previous studies indicating obvious differences in physiological function and potency between FLP peptides encoded on the same gene in H. glycines , Panagrellus redivivus , or C. elegans ( Masler et al, 2012 ; Atkinson et al, 2016 ). It has been documented that a single FLP receptor can be activated by multiple FLPs, whereas the potency of receptor activation by structurally similar FLPs is different ( Rogers et al, 2003 ; Mertens et al, 2005 ; Cohen et al, 2009 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Hg-FLP-22b and Hg-FLP-22c displayed significant stimulatory effects on head movement and stylet penetration ability compared with Hg-FLP-22a, suggesting the two peptides may be significantly more active isoforms of Hg-FLP-22 for activation of putative cognate receptors. Similar observations were also reported by previous studies indicating obvious differences in physiological function and potency between FLP peptides encoded on the same gene in H. glycines , Panagrellus redivivus , or C. elegans ( Masler et al, 2012 ; Atkinson et al, 2016 ). It has been documented that a single FLP receptor can be activated by multiple FLPs, whereas the potency of receptor activation by structurally similar FLPs is different ( Rogers et al, 2003 ; Mertens et al, 2005 ; Cohen et al, 2009 ).…”
Section: Discussionsupporting
confidence: 91%
“…Applications of synthetic Hg-FLP-22 peptides (FLP-22b and FLP-22c) significantly increased the head movement frequency of H. glycines . This is similar to the observation which showed that FLP-6 and FLP-14, both highly conserved single-copy peptides in nematode species ( Peymen et al, 2014 ), also have significant stimulatory effects on the anterior movement frequency of H. glycines and M. incognita ( Masler et al, 2012 ). Once hatched from eggs, the infective J2s of PPN need to quickly move toward host roots and penetrate the cortex layer cells via thrusting their stylet before their energy reserves are depleted ( Perry, 1996 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations